Question
upstudy study bank question image url

If possible, solve the system of equations. Use any method. If there is not a unique solution to the system, state a reason. \[ \begin{array}{ll}4 x-y=22 & \text { (1) } \\ 7 x+3 y=48 & \text { (2) }\end{array} \]

Ask by Hobbs Rowe. in the United States
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The system has a unique solution: \( x = 6 \) and \( y = 2 \).

Solution

To solve the system of equations: \[ \begin{cases} 4x - y = 22 \quad \text{(1)} \\ 7x + 3y = 48 \quad \text{(2)} \end{cases} \] we can use the **substitution method**. Here's a step-by-step solution: ### Step 1: Solve Equation (1) for \( y \) Starting with equation (1): \[ 4x - y = 22 \] Subtract \( 4x \) from both sides: \[ -y = -4x + 22 \] Multiply both sides by \( -1 \) to solve for \( y \): \[ y = 4x - 22 \quad \text{(3)} \] ### Step 2: Substitute \( y \) into Equation (2) Now, substitute equation (3) into equation (2): \[ 7x + 3y = 48 \] Replace \( y \) with \( 4x - 22 \): \[ 7x + 3(4x - 22) = 48 \] ### Step 3: Simplify and Solve for \( x \) Expand the equation: \[ 7x + 12x - 66 = 48 \] Combine like terms: \[ 19x - 66 = 48 \] Add \( 66 \) to both sides: \[ 19x = 114 \] Divide both sides by \( 19 \): \[ x = \frac{114}{19} = 6 \] ### Step 4: Find \( y \) Using the Value of \( x \) Now that we have \( x = 6 \), substitute this back into equation (3): \[ y = 4(6) - 22 = 24 - 22 = 2 \] ### Conclusion The system has a **unique solution**: \[ x = 6, \quad y = 2 \] --- **Verification:** To ensure the solution is correct, plug \( x = 6 \) and \( y = 2 \) back into both original equations. 1. **Equation (1):** \[ 4(6) - 2 = 24 - 2 = 22 \quad \text{✓} \] 2. **Equation (2):** \[ 7(6) + 3(2) = 42 + 6 = 48 \quad \text{✓} \] Both equations are satisfied, confirming that \( x = 6 \) and \( y = 2 \) is indeed the correct solution.

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Mind Expander

To solve the system of equations, we'll use the substitution or elimination method. Let's use substitution for this example. From equation (1): \[ 4x - y = 22 \] We can rearrange it to express \( y \) in terms of \( x \): \[ y = 4x - 22 \] Now, substitute \( y \) into equation (2): \[ 7x + 3(4x - 22) = 48 \] Expand and simplify: \[ 7x + 12x - 66 = 48 \] Combine like terms: \[ 19x - 66 = 48 \] Now, isolate \( x \): \[ 19x = 48 + 66 \] \[ 19x = 114 \] \[ x = \frac{114}{19} \] \[ x = 6 \] Now, substitute \( x = 6 \) back into the equation for \( y \): \[ y = 4(6) - 22 \] \[ y = 24 - 22 \] \[ y = 2 \] Thus, the solution to the system of equations is \( x = 6 \) and \( y = 2 \). To verify, we can plug these values back into the original equations: For (1): \[ 4(6) - 2 = 22 \] \[ 24 - 2 = 22 \] (True) For (2): \[ 7(6) + 3(2) = 48 \] \[ 42 + 6 = 48 \] (True) The solution checks out! Therefore, the unique solution to the system is \( (x, y) = (6, 2) \).

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy